Computational Studies for CO2 Capture in Microstructured Membrane Reactors - Harkou, Eleana (Department of Chemical Engineering, Faculty of Geotechnical Sciences and Environmental Management, Cyprus University of Technology, 2021)
Carbon dioxide (CO2) is one of the major atmospheric greenhouse gases. The continuous increase of CO2 concentration and its long atmospheric lifetime may cause long-term negative effects on the climate. It is important to develop technologies in order to capture and minimize those emissions into the atmosphere. The objective of this work is to design and study theoretically a microstructured reactor in order to be used as a capture system. This work focuses on the geometrical parameters that affect the uniform flow distribution in a microreactor. The flow distribution was firstly tested on 2D simulations and then the results were approved by 3D CFD models. Moreover, in order to maximize the throughput of the system, four parallel microplates were used where even flow distribution was achieved into each layer of the microreactor.
Keywords: CO2 capture; Microreactors; Uniform flow distribution; CFD simulations; Umbering-up microreactor.